Association of a Distal Intradural-Extracranial Posterior Inferior Cerebellar Artery Aneurysm With Chiari Type I Malformation: Case Report. Issue 4 (October 2015) - Mascitelli, Justin R.; Ben-Haim, Sharona; Paramasivam, Srinivasan; Zarzour, Hekmat K.; Rothrock, Robert J.; Bederson, Joshua B.
Abstract : BACKGROUND AND IMPORTANCE: Distal extracranial posterior inferior cerebellar artery (PICA) aneurysms are very rare lesions and have not been previously reported in association with a Chiari type I malformation (CMI). CLINICAL PRESENTATION: A 56-year-old woman with a distal, low-lying, intradural-extracranial PICA aneurysm presented with a subarachnoid hemorrhage and was treated with coil embolization. The patient presented again 1 month later with symptoms of a CMI and was found to have tonsillar herniation and a large syrinx that appeared to be exacerbated by the coil mass. The patient was re-treated with a suboccipital craniectomy, C1-2 laminectomy, aneurysm trapping and excision, end-to-end PICA anastomosis, and expansile duraplasty. CONCLUSION: Although just a single case, important teaching points regarding the angiographic appearance of a CMI and treatment options for distal PICA aneurysms that are situated below the foramen magnum can be learned. A low-lying caudal PICA loop should trigger a workup for a CMI. Caution should be taken when using coil embolization for aneurysms in the high cervical spinal canal. Bypass with aneurysm trapping and excision may be a superior treatment option in these cases because the posterior fossa and high cervical canal can be concomitantly decompressed. To our knowledge, this is the only case reported of a distal intradural-extracranial PICA aneurysm associated with a CMI. ABBREVIATIONS: CMI, Chiari type I malformation FM, foramen magnum PICA, posterior inferior cerebellar artery SAH, subarachnoid hemorrhage